Reducing Cache Pollution in GDFS Cache Algorithm Using Normalized Google Distance (NGD) for Semantic Similarity - الديباجة ايهاب (Latakia University Journal -Engineering Sciences Series, 2021)
Cache is considered as one of techniques that effectively contributes in enhancing performance of information retrieval systems. Web cache which is the cache technology specified for web is one of the tools for enhancing response time in web-bases information systems (WIS). That’s can be done by algorithms which varying in its replacement function. We study in this paper how to reduce hot cache pollution and cold cache pollution which may affects GDFS (Greedy Dual Frequency Size) web cache algorithm. This algorithm is considered as a fundamental web cache algorithm, by improving replacement function using Normalized Google Distance (NGD) between cache objects. Results shows that employing semantic similarity concept to GDFS replacement function have had reduced cache pollution by improving the control of existence of objects in cache memory and collaboration with original function of GDFS algorithm in evaluation the existence of objects in cache and thus improving hit rate of objects from cache memory instead of original data source